Carbon dynamics in a large ultra-oligotrophic epishelf lake (Beaver Lake, Antarctica) during summer - Laybourn-Parry, J; Madan, NJ; Marshall, WA; Marchant, HJ; Wright, SW (2006)
1. Microbial plankton dynamics in an ultra-oligotrophic epishelf lake (Beaver Lake, Antarctica) were investigated over an austral summer (December 2002 to January 2003). The aim was to characterise carbon cycling in an environmentally extreme lake. 2. The lake had an unusual temperature profile with peak temperatures of 1.3-1.9 C between 20 and 25 m. Photosynthetically active radiation penetrated to the lake bottom (110 m) on occasions. The ice cover underwent marked thinning and melting during the study period. 3. Chlorophyll a concentrations were consistently low, usually below 1 lg L)1, with highest concentrations close to the lake bottom, where the photosynthetic elements showed strong autofluorescence. Mean photosynthetic nanoflagellates ranged between 34.9 104 L)1 +/- 33.5 (23rd December) and 130.9 104 L)1 +/- 112.3 (4th December). Highest photosynthetic activity was usually recorded below 25 m. Rates of carbon fixation varied between 0.089 lg C L)1 h)1 +/- 0.002 and 0.579 lg C L)1 h)1 +/- 0.156. Primary production was limited by low temperature and orthophosphate availability. 4. Mean bacterial concentration throughout the water column ranged between 9.3 107 L)1 +/- 1.2 (23rd December) and 14.0 107 L)1 +/- 1.8 (28th January). Bacterial production was low, less than 10% of primary production and ranged between 2.1 ng C L)1 h)1 +/- 0.8 and 12 ng C L)1 h)1 +/- 0.9. Highest rates coincided with times of highest primary production. On occasion dissolved organic carbon (DOC) concentrations dropped to 20 lg L)1, probably below accurate limits of detection, suggesting that carbon substratum and phosphorus may have limited bacterial growth. 5. Heterotrophic nanoflagellates varied significantly over the summer from a mean of 26.6 104 L)1 +/- 14.2 (23rd December) to 133.8 104 L)1 +/- 33.5 (14th December). They imposed a significant grazing impact on the bacterioplankton, removing in excess of 100% of bacterial production in December. 6. The total organic carbon pool [DOC and particulate organic carbon (POC)] was ...